Methods Of Resolving Mukhtalif Hadith Perspective Of Imam Al-Shafi'i - Safdhinar Muhammad An-Noor; Fathira Nadia Makka; Ahmad Luthvan Habiburrahman (Jurnal Indonesia Sosial Teknologi, 2023)
This article recognizes the necessity of dealing with the reality of contradictory traditions and the need for theoretical solutions to resolve them. This is where Imam al-Shafi'i initiated and came up with alternative theories that can be used to solve the irregularities and resolve the incongruity of the traditions that seem to contradict each other. This study aims to find out the methods used by Imam Shafi'i in his resolution of mukhtalif traditions. The method used is descriptive-qualitative. This type of research is literature research. The results of this study indicate that there are several stages of theory and methodology used by Imam al-Shafi'i in resolving mukhtalif traditions consisting of the Jammu wa al-taufiq method, the naskh method, the target method, and tawaqquf. In detail, the Jammu wa taufiq method is further classified by solving through the usual fiqh approach, contextual understanding, correlative understanding, and by the take method. In addition, a settlement model was also found in the problem of tanawwu' al-ibadah. Knowing these details can be used as a basis for thinking in resolving traditions that are assumed to contradict each other. So that the substance